The Effects of Gamification in Space Exploration Learning - Chiu, Po Chan; Melvin Jangga, Rupitan; Kuok, King Kuok; Hamizan, Sharbini; Noor Hazlini, Borhan; Alvin, Yeo (Semarak Ilmu Publishing, 2024)
Gamification in education has grown in popularity in recent years. However, gamification in space exploration education receives limited attention. This paper introduces Mission to the Star, an innovative online learning plat form designed for primary students, immersing them in the fascinating journey of NASA's Parker Solar Probe as it ventures closer to the Sun. Embarking on an extraordinary mission, player s assume the role of a spacecraft and navigate toward the Sun's atmosphere, learning vital information along the way. Research findings demonstrate that the incorporation of gamification elements such as badges, score points, certificates, leaderboards, and more, has notably enhanced student learning in comprehending the Parker Solar Probe mission. By integrating these gamified elements, students are motivated to actively participate, benefiting from an interactive and enjoy able learning experience. Mission to the Star holds significance in education as it provides an interactive exploration encounter that sparks the curiosity and enthusiasm of young learners toward space exploration and science knowledge.